The Peruvian Economy In 1973 And Its Perspectives - Portocarrero, Felipe (Universidad del Pacífico, 1974)
This article analyzes the Peruvian economic situation in 1973, its sectoral evolution, the development of investment, agreements with the imperialist capital, the economic policy and the perspectives for the future.